La sangre es la vida: a la caza del vampiro semítico - Guadalupe Ingelmo, S. (ISIMU, 2016)
Human communities of any time, including the mesopotamian one, have developed world-wide the myth of the vampire one apart each other. It shows undoubtedly that we could find a worry inherent to the human being in the foundations of this myth: his mortal character. In ancient times the vampire was only a female being, while after the female vampire survives beside the male vampire with a function always secondary. The vampire suffers, what we could say, a change of sex with absolute certainty in modern times. It's then that the male vampire character, what we know so well by means of literature and films, the prototype that Bram Stoker would settle definitively, grows. Finally we would like to remind that the vampire phenomenon is culturally too complex to try to reduce it to a medical pathology. Even though medicine could explain the relatively recent cases of balkan vampirism more or less satisfactory, we can't forget that the myth of the vampire sinks his roots millennia behind, penetrating into the most primitive fear of the most primitive human being.